Teacher-Facilitated Plugged Coding for Early Childhood Computational Thinking - Fifi Syara Wahyu; Mallevi Agustin Ningrum; Yes Matheos Lasarus Malaikosa; Andi Kristanto; Nurul Istiq'faroh; Mohammad Syahidul Haq; Ruqoyyah Fitri (Academia Open, 2026)
General Background Early childhood education is increasingly required to respond to digital transformation by integrating technology-based learning experiences that support foundational cognitive skills. Specific Background One emerging approach is plugged coding, which introduces basic programming concepts through digital devices in play-based classroom activities for children aged 5–6 years. Knowledge Gap Despite growing attention to coding in early childhood, limited empirical evidence explains how teacher roles, readiness, and pedagogical strategies shape the development of computational thinking within real classroom contexts, particularly under practical digital constraints. Aims This study aims to examine the implementation of plugged coding learning in early childhood education and to analyze the role of teachers in supporting children’s computational thinking development. Results Using a descriptive qualitative case study at a public kindergarten, findings show that children demonstrated indicators of computational thinking, including sequencing, pattern recognition, and initial debugging, while teachers employed scaffolding strategies such as prompting questions, visual demonstrations, and guided reflection. However, variations in teacher readiness and challenges related to device availability, technical issues, and screen-time management were evident. Novelty This study provides an in-depth qualitative account of teacher-mediated plugged coding practices aligned with a play-based curriculum in an authentic early childhood setting. Implications The findings underscore the importance of continuous teacher training, adequate digital infrastructure, and pedagogically appropriate learning media to support sustainable integration of plugged coding in early childhood education. Highlights: Children demonstrated sequencing, pattern recognition, and basic error correction during technology-supported activities. Pedagogical scaffolding and play-based design were central to guiding learning processes. Limited devices and teacher digital readiness shaped classroom implementation strategies. Keywords: Computational Thinking, Early Childhood Education, Plugged Coding, Teacher Role, Digital Learning